Architecture and regulation of the HIV-1 assembly and holding compartment in macrophages. - Welsch, S; Groot, F; Kräusslich, H; Keppler, O; Sattentau, Q (2011)
Productive infection of macrophages is central to HIV-1 pathogenesis. Newly formed virions bud into a tubular membranous compartment that is contiguous with the plasma membrane. However, little is known about the structure of this compartment and its potential regulation by infection. Here we characterized this compartment in macrophages using electron tomography and electron microscopy with stereology. We found an intricate, interconnected membrane network that constitutes a preexisting physiologic structure in macrophages but which expands in size upon HIV-1 infection. Membranes required for this expansion were apparently derived from preexisting pools of plasma membrane. Physical connections between this compartment and the extracellular milieu were frequently made by tube-like structures of insufficient diameter for virion passage. We conclude that HIV-1 induces the expansion of a complex membranous labyrinth in macrophages in which the virus buds and can be retained, with potential consequences for transmission and immune evasion.